Speech Competence of Primary School Students: Cognitive Approach - Hreb, Maria Mykhailivna; Hrona, Nataliia; Chumak, Viktor; Vyshnyk, Olena; Hreb, Volodymyr (Journal of History Culture and Art Research, 2020)
This article reveals the peculiarities of speech competence formation of primary school students in the conditions of cognitive approach realization. The article found out that the formation of speech competence of primary school students is facilitated by the cognitive teaching of language. This approach teaches students to consciously construct expressions in specific life situations. It has been proved that speech competence is an integral quality of a person, manifested in the ability and willingness to use linguistic means, regularities of their functioning for the construction, and understanding of speech utterances in accordance with the communicative purpose. To assess the level of speech competence formation, we relied on indicators of the category "Application" by Bloom’s taxonomy, the Oxford Cambridge 2000 program, the modified methodology "КОС-22", specific norms of competence pedagogy. It has been found that mastering cognitive skills enables a person to work with information independently in the process of acquiring it (mastering knowledge). It is proved that the text represents speech competence. It is substantiated that the following types of exercises are leading in the work on the text: analytical, associative, and research. It is proved that the cognitive approach is based on the provisions of cognitive psychology, which implies a reliance on the principle of consciousness in the process of speech competence formation in primary school students. This approach directs the educational process to communicative activities, ensuring the proper level of students’ speech competence.